A study of tsunami-like solitary wave transformation and run-up over fringing reefs. (1st February 2018) - Yao, Yu; He, Fang; Tang, Zhengjiang; Liu, Zengsheng
Abstract: After the 2004 Indian Ocean tsunami, the effectiveness of fringing reefs in protecting coastlines from tsunami-induced inundation has aroused great attention in the post-tsunami surveys. To better understand the role of fringing reefs in the mitigation of a tsunami hazard, laboratory experiments were conducted in a wave flume to study the transformation and run-up of tsunami-like solitary waves over various fringing reef profiles. The effects of incident wave height, reef-flat submergence, lagoon width and reef surface roughness were examined. Cylinder arrays were employed to create artificial roughness elements on the reef surface. Empirical formulas based on the experimental data were also proposed for the wave run-up. The ratio of the reef flat submergence to the incident wave height was always found to be the dominant parameter to characterize the wave run-ups over various tested reef profiles. Subsequently, a numerical model based on the improved Boussinesq equations including the drag effect of roughness elements was validated by the experimental data. The validated model was then applied to investigate the impacts of variations of reef morphologies (fore-reef slope, back-reef slope, reef-flat width, reef-crest width) on the solitary wave run-up. Highlights: Tsunami-like solitary wave transformation and run-up over various fringing reef profiles were investigated experimentally. The effects of incident wave height, reef-flat submergence, lagoon width and reef surface roughness were examined. Wave run-up was found to depend primarily on the ratio of the reef flat submergence to the incident wave height. A numerical model based on the improved Boussinesq equations including the roughness drag effect was validated. The validated model was applied to investigate the impacts of variations of reef morphologies on the solitary wave run-up.